Foreign direct investment, growth, and spillover effects - Evans, Frank (Kansas State University, 2019)
The literature on foreign direct investment is expansive but somewhat fragmented, and as a result, can sometimes be hard to disentangle in a meaningful way. The purpose of this paper is to examine foreign direct investment in a comprehensive but straightforward way. We hope to do this by examining FDI in a generalized and historical sense, FDI’s relationship with growth, and the means by which FDI influences growth and productivity.
Keywords: Foreign Direct Investment; Growth; Spillover EffectsFDI